Putative Novel Species of Genus Capnocytophaga, Capnocytophaga stomatis Bacteremia in a Patient with Multiple Myeloma after Direct Contact with a Cat - Shinohara, Koh; Tsuchido, Yasuhiro; Suzuki, Michio; Yamamoto, Kojiro; Okuzawa, Yasutaro; Imaoka, Koichi; Shimizu, Tsunehiro (Internal Medicine, 2022)
Capnocytophaga species are among the typical zoonotic pathogens causing infections following direct contact with animals. Recently, a putative novel species of zoonotic Capnocytophaga, Capnocytophaga stomatis, was reported. We herein report the first case of bacteremia caused by C. stomatis. A woman in her 80s with multiple myeloma who was receiving bortezomib and dexamethasone therapy was admitted to our hospital with a 2-day history of a fever and right calf redness. She was often licked by her cat. On a blood culture, thin, Gram-negative rods were detected, which were identified as C. stomatis by whole-genome sequencing. The patient was successfully treated with ampicillin-sulbactam treatment. Our case highlights the pathogenic potential of the putative novel Capnocytophaga, C. stomatis, in immunocompromised hosts.